Mycoplasma infection aggravates cardiac involvements in Kawasaki diseases: a retrospective study - Lu, Guoyan; Li, Xing; Tang, Jie; Jin, Yuxi; Wang, Yang; Zhou, Kaiyu; Li, Yifei (Frontiers in Immunology, 2024)
Background: Mycoplasma pneumonia (MP) infection serves as a substantial cofactor in Kawasaki disease (KD) among patients. Although the dominant issue triggering KD has recently focused on MP infection, the complete demonstration of the relationship between MP infection and KD remains elusive. This study endeavors to scrutinize and compare the clinical manifestations and cardiac involvement between MP-triggered KD and noninfection-associated KD.. Method: This retrospective study (2023-039, approved by the Institutional Review Board of West China Second University Hospital of Sichuan University) encompassed 247 consecutive patients diagnosed with KD between June 2017 and December 2022. Patients were categorized into two groups: the MP group (n=38) and the non-MP group (n=209). Univariable analysis was utilized to discern differences in clinical features, severity of inflammation, and initial or persistent cardiac complications between the two groups.The MP group exhibited a more intricate clinical profile compared to the non-MP group, characterized by prolonged hospital stays, a higher incidence of incomplete KD, and elevated comorbidities. Additionally, MP infection correlated with severe hematological disorders, coagulation dysfunction, and myocardial injuries. Our findings revealed that MP infection led to prolonged inflammation post-initial treatment with intravenous immunoglobulin. While initial cardiac assessments failed to discern disparities between the two groups, MP infection notably exacerbated coronary artery aneurysms (CAAs), resulting in sustained dilation. Conclusions: Recognizing MP infection as a significant infectious factor associated with KD is imperative. In KD patients, MP infection significantly prolongs inflammation and causes hematological disturbances during the initial treatment phase. Moreover, the presence of MP infection exacerbates the progression of CAAs and myocardial injuries during the subacute phase of KD, consequently contributing to the persistence of CAAs.